The relationship between self-efficacy and compliance with hemodialysis in chronic kidney failure patients in the hemodialysis room at Wakatobi Regional Hospital - La Ode, Agustiwarno; Ekawati , Dian; Ratnasari , Kiki (Program Studi Keperawatan, Politeknik Negeri Subang, 2024)
Background: Self-efficacy, or an individual's belief in their own abilities, plays a crucial role in determining how they respond to different circumstances. In patients with chronic kidney disease undergoing hemodialysis, self-efficacy can significantly impact treatment adherence, which is essential for positive health outcomes. However, the relationship between self-efficacy and adherence in this population remains underexplored. Purpose: This study aims to investigate the relationship between self-efficacy and adherence to hemodialysis in patients with chronic kidney disease at Wakatobi Regional Hospital. Methods: A cross-sectional quantitative study was conducted with a purposive sample of 57 respondents. Data were collected using validated self-efficacy and adherence questionnaires. The Spearman rank correlation test was employed to analyze the relationship between self-efficacy and adherence. Results: The findings revealed that 63.2% of respondents exhibited high self-efficacy, and 91.2% were categorized as adherent to their hemodialysis treatment. Statistical analysis demonstrated a significant positive relationship between self-efficacy and adherence (p=0.000), indicating that patients with higher self-efficacy tend to adhere more consistently to their treatment regimen. Conclusion: There is a significant relationship between self-efficacy and adherence to hemodialysis in patients with chronic kidney disease at Wakatobi Regional Hospital. These findings suggest that enhancing self-efficacy may improve adherence in this patient population. Future research should explore this relationship in other settings and with different study designs to confirm and expand on these results.